SYAIR CERMIN ISLAM DALAM KAJIAN SASTRA PROFETIK - Sahril, Sahril; Nurelide, Nurelide (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2023)
Syair Cermin Islam is a Malay oral text which contains Islamic teachings related to amar ma'ruf and nahi mungkar. This poetry text has elements of transcendence, namely going beyond human experience which is prophetic in nature. This research aims to describe the prophetic reality in the text of Syair Cermin Islam which is still relevant in today's modern world. This research uses a dynamic-structuralism (semiotic) approach and data analysis is carried out using content analysis techniques. The semiotic approach is a sign system approach. Signs in literary literature come in the form of texts, both within the text structure and outside the text structure. Of course it will contribute to the understanding of prophetic reality. The data analysis method refers to the process of determining the unit of analysis which consists of poetry text. The main findings in this research are: Firstly, prophetic reality in the aspect of meaning reconstruction and interpretation related to the transcendence of amar ma'ruf and nahi munkar, with divine awareness and longing for eternal life. Second, the prophetic reality in the liberation aspect is related to the relationship between actions and the consequences received for those actions. The essence of the findings from the analysis of the text of Syair Cermin Islam is in the form of a command to do good deeds and abandon bad deeds so that humans are safe in this world and in the afterlife.